Penerapan Teknologi Pengemasan dan Digital Marketing Pengelolaan Ikan Asin pada Kelompok Usaha Bersama Putri Duyung Belawan - Rossevelt, Franklin Asido; Lubis, Muhammad Arif; Harahap, Edy Syahputra (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
KUBE Putri Duyung faces productivity and marketing constraints due to manual packaging methods and traditional sales strategies, leading to salted fish stockpiling and declining selling prices. This community service initiative aims to enhance the group's competitiveness through the integration of packaging technology and digital marketing. The methods employed include socialization, training, technology implementation (drying machine, vacuum sealer, continuous sealer), intensive mentoring, and ongoing evaluation. As a result, production capacity increased by 25-50%, time efficiency improved by 25%, and sales grew by 30% through digital platforms. This program successfully transformed KUBE Putri Duyung into a competitive and sustainable MSME in the Society 5.0 era, aligning with the achievement of SDGs numbers 8, 9, and 12.